Pemanfaatan ID3 dan Influence Map pada Game Turn-Based Strategy - Utomo, Vincent; -, Liliana; Budhi, Gregorius Satia (Jurnal Infra, 2015)
One of interesting aspect in game is virtual enemy (AI) as enemy to the player. This aspect is important to give challenge to the player, especially for a single player game. One game that requires such AI is a turn-based strategy game. To be able to create an interesting and challenging AI for the player, it is require equally strong and dynamic AI.To create such AI, ID3 and Influence Map will be used as the base of the AI used in turn-based strategy game. Applications made include ID3 training software and Influence Map class inside the game that will be used. ID3 System is made to have the ability to process continuous data.The results showed that the ability to create a decision tree by ID3 is greatly influenced by the training data used. The results also showed that the propagation method used for the Influence Map system can be set to suit the requirements in the game.